2015
DOI: 10.3920/wmj2014.1814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fungicide application to controlFusarium head blight and 20Fusarium andAlternaria mycotoxins in winter wheat (Triticum aestivum L.)

Abstract: Azole fungicides have been reported to be the most effective active substances in the control of Fusarium Head Blight (FHB) and in the reduction of the main mycotoxins that occur in cereal grain, such as deoxynivalenol (DON). Four field experiments have been conducted in North West Italy, over a period of 2 growing seasons, in order to evaluate the effect of azole fungicide (prothioconazole) applications on the prevalence of emerging mycotoxins in common winter wheat under naturally-infected field conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
2
17
0
3
Order By: Relevance
“…Those toxins have been detected in similar concentrations as DON in naturally contaminated grain [22]. In the present study, both acid treatments were effective in reducing these mycotoxins, whereby a higher effect was achieved after soaking in LA.…”
Section: Discussionsupporting
confidence: 55%
“…Those toxins have been detected in similar concentrations as DON in naturally contaminated grain [22]. In the present study, both acid treatments were effective in reducing these mycotoxins, whereby a higher effect was achieved after soaking in LA.…”
Section: Discussionsupporting
confidence: 55%
“…were detected together with traces of those produced by Alternaria spp. [69]. Commonly, mycotoxinogenic fungi are divided into two groups: preharvest (mainly Fusarium species) and postharvest (mainly Aspergillus and Penicillium species) fungi.…”
Section: Alternaria Aspergillus Mycotoxins and Other Metabolitesmentioning
confidence: 99%
“…Scarpino et al . () reported that azole fungicides are the most effective active substances in controlling FHB and in the reduction of the foremost mycotoxins in cereal grain, e.g. DON.…”
Section: Chemical Management Strategiesmentioning
confidence: 99%